(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
Female education in Liceus, in Rio Grande do Sul, has been developed since the 19th century, but mainly under the aegis of the State, in the early 20th century. The bibliographic and documental research sought to find relationships between female education and teaching in arts and crafts. The investigation in theses, dissertations, articles and periodicals showed the permanent mark of the curriculum aimed at training limited to the domestic horizon. Thus, in relations with literature and cinema, we perceive the maintenance of fixed patterns of behavior and female insertion, in which the issue of gender is always marked by domesticity and care for the house and children.